2018
DOI: 10.1063/1.5040458
|View full text |Cite|
|
Sign up to set email alerts
|

Measuring the wall depletion length of nanoconfined DNA

Abstract: Efforts to study the polymer physics of DNA confined in nanochannels have been stymied by a lack of consensus regarding its wall depletion length. We have measured this quantity in 38 nm wide, square silicon dioxide nanochannels for five different ionic strengths between 15 mM and 75 mM. Experiments used the Bionano Genomics Irys platform for massively parallel data acquisition, attenuating the effect of the sequence-dependent persistence length and finite-length effects by using nick-labeled genomic DNA with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 72 publications
3
14
0
Order By: Relevance
“…An approximate way to account for electrostatic repulsion between the DNA chains and silica/glass surfaces involves the use of an effective depletion length, which decreases the apparent slit height . These effects are less significant in our experiments than in many previous reports because the silica surface charge is significantly reduced by silanization and because the DNA is heavily screened by tetracationic intercalating dye.…”
supporting
confidence: 84%
“…An approximate way to account for electrostatic repulsion between the DNA chains and silica/glass surfaces involves the use of an effective depletion length, which decreases the apparent slit height . These effects are less significant in our experiments than in many previous reports because the silica surface charge is significantly reduced by silanization and because the DNA is heavily screened by tetracationic intercalating dye.…”
supporting
confidence: 84%
“…By reducing w/p ratios to 1/4 9 , his simulation predicted X/L approaches the unity more closely. On the other hand, Bhandari et al recently reported X/L = 90.39% in 38 nm square channels when IS = 16.9 ~ 72.2 mM, w/p = 0.13 ~0.22 [49]. Their results follow Equation (11) as shown as shown as X symbols in Figure 5A.…”
Section: Resultsmentioning
confidence: 62%
“…DNA stretch ratio ( X / L ) dependent on p and w : ( A ) The black line was drawn by Equation (11) and the gray line was down-shifted by 0.13 (Equation (12)). The gray symbols were obtained from other references: X : 38 nm nanochannel experiment [49]; open circles: simulation for p=4w; open diamond: simulation for p=w [50]. The blue line was the best fit for the de Gennes regime (Equation (14)).…”
Section: Figurementioning
confidence: 99%
“…Despite being conceptually different, such approximation proved to be reasonably accurate when comparing simulations to experiment. 30,31 Hence, in interpreting our model results, our simulations are equivalent to running experiments in a channel of size D geo = D + w if excluded-volume effects are to be considered.…”
Section: ■ Modelmentioning
confidence: 99%
“…The confinement potential mimics hard wall repulsion that allows the WLC to explore D range in both the X and Y directions regardless of the excluded-volume effects. For an experiment conducted in a channel size D , the physical space accessible to the DNA is reduced by the amount δ to account for electrostatic and excluded-volume interaction with channel walls . Different models were proposed to quantify the wall depletion length δ at varying levels of accuracy. , However, it is common to make the approximation that δ = w , where the excluded volume between a charged rod and a functionalized hard wall is taken to be similar in magnitude to the excluded volume between two charged rods of the same linear charge density when mapped to equivalent neutral rods.…”
Section: Modelmentioning
confidence: 99%